Comparison of InSight Homestead Hollow to Hollows at the Spirit Landing Site. Issue 7 (14th July 2020) - Weitz, Catherine M.; Grant, John A.; Golombek, Matthew P.; Warner, Nicholas H.; Hauber, Ernst; Ansan, Veronique; Wilson, Sharon A.; Charalambous, Constantinos; Williams, Nathan; Calef, Fred; Pike, W. Thomas; Lethcoe‐Wilson, Heather; et al.
Abstract: The InSight spacecraft landed within an 27‐m diameter highly degraded impact crater, informally called Homestead hollow, that was disturbed during landing by pulsed retrorockets that blew out dust and scoured loose sand around the landing site. In order to provide insight into what the surface of Homestead hollow originally looked like before landing and to further characterize hollow physical properties, we examined images of similar hollows taken by the Spirit rover at the Gusev landing site. Hollows at both sites are characterized by a quasi‐circular appearance with little or no crater rim still visible and a bright interior with fewer and smaller rock sizes relative to the surrounding plains. Resolvable clast lengths (>2 mm) measured in Laguna hollow at the Spirit site and Homestead hollow are comparable with most clasts between 3 and 7 mm in length. Measurements of clast shapes show that those in Laguna hollow are slightly more elongate relative to those in Homestead hollow, although this may be an artifact of the differing viewing geometry and (or) a thicker dust mantle obscuring the full shape of clasts at Laguna hollow. The soils at both hollows show evidence for cohesion and a duricrust, with a trench dug at Laguna hollow and pits exposed at Homestead hollow exhibiting steep slopes, overhanging layers, and clods of soils. The similarities in morphology and physical properties of hollows at two different landing sites suggest recent environmental conditions that degrade and infill impact craters are comparable and pervasive for equatorial volcanic plains on Mars. Key Points: Degraded impact craters called hollows at both the InSight and Spirit landing sites appear similar in morphology from orbital and surface images The clasts within Homestead hollow are similar in size and shape to those within Laguna hollow, with most resolvable clasts ranging from 3–7 mm in length The hollow similarities at two different landing sites suggest recent environmental conditions that degrade and infill craters are comparable and pervasive